1994
DOI: 10.1111/j.1574-6968.1994.tb06707.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalisfimbriae and their synthetic peptides induce proinflammatory cytokines in human peripheral blood monocyte cultures

Abstract: Porphyromonas gingivalis fimbriae as well as synthetic peptides that mimic the fimbrial subunit protein, which includes the amino acid sequence XLTXXLTXXNXX, induced high production of proinflammatory cytokines such as interleukin-1 beta, interleukin-6, interleukin-8, tumor necrosis factor-alpha in human peripheral blood monocyte/macrophage cultures. Responses induced by some peptide segments were comparable to those induced by Escherichia coli lipopolysaccharides. A chemically modified peptide analogous to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The fimbrial subunit FimA from P. gingivalis 381 (which is similar to strain ATCC 33277) has also been reported to protect rats and mice when challenged with the same strain (12,40). However, the fimA gene is inactive in the virulent W50 strain, and thus the protein is not expressed (57) a Antibody titers are expressed as the dilution factor determined from sigmoidal dilution curves which produced an OD 414 value fivefold greater than the background level in the ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fimbrial subunit FimA from P. gingivalis 381 (which is similar to strain ATCC 33277) has also been reported to protect rats and mice when challenged with the same strain (12,40). However, the fimA gene is inactive in the virulent W50 strain, and thus the protein is not expressed (57) a Antibody titers are expressed as the dilution factor determined from sigmoidal dilution curves which produced an OD 414 value fivefold greater than the background level in the ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. gingivalis-killed whole cells and sonicated cell surface extracts have been reported to reduce bone loss in the rat and nonhuman primate models of periodontitis (12,43). Purified fimbrial protein from P. gingivalis strains ATCC 33277 and 381 have also been reported to confer protection in the murine lesion model and the rat periodontitis model (12,40). Ogawa et al (40) have reported that peptide immunogens derived from the fimbriae of P. gingivalis 381 reduced the lesion size by up to 88%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These LRRs contain multiple LT motifs which, though not as closely positioned in the primary sequence as the proposed LTXXLT proinflammatory motif (37), are predicted to be close together in the tertiary structure of the protein (21). The amphipathic properties of LRR proteins may explain why such proteins are involved in adherent interactions and why at least half of them participate in signal transduction pathways (21).…”
Section: Vol 9 2002 Cytokine Induction By Virulence Proteins Via Tlmentioning
confidence: 99%
“…The functional versatility of fimbriae arises from their ability to interact with various dental or epithelial substrates and extracellular molecules, such as fibrinogen, fibronectin, and lactoferrin (summarized in reference 23). Native fimbriae, derived synthetic peptides, and recombinant fimbrillin (rFimA), the 41-kDa structural subunit of fimbriae, can induce the expression of proinflammatory cytokines such as tumor necrosis factor ␣ (TNF-␣) and IL-1␤ in human and mouse monocytes/macrophages (37,43). It has been shown that ␤2 integrins (CD11/ CD18) serve as a cellular receptor for fimbria-induced cytokine responses in mouse macrophages (49).…”
mentioning
confidence: 99%